Analisis Yuridis Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Dalam Bidang Ketenagakerjaan - Winsherly Tan (Faculty of Law, Maranatha Christian University, 2022)
After the enactment of Act Number 11 of 2020 concerning Job Creation, we consider that a more comprehensive study is needed for businessman and academic to sharpen understanding related to the latest labor law regulations. So, we took the initiative to compile this article manuscript in the hope of contributing thought related to the substance to be discussed, namely changes in labour law in the Job Creation Law. The Discussion tha will be discussed in this article is the forms of changes in labor law and the substance of the changes contained in the Job Creation Law. This article aims to provide a comprehensive understanding related to the labor law after revision of Act Number 13 of 2003 concerning Employment in the Acr number 11 of 2020 concerning Job Creation. By using this type of normative research, it is hope that this research can provide a comparison of previous labour law (before revision) with the post revision. The result of the research in this article describes the various forms of changes in labor law in the form of table descriptions to facilitate understanding regarding the substance of these changes.